Health and culture in a south Indian village - Matthews, C. M. E. (New Delhi, 1979)
The study described in this book was undertaken as a basis for future health education work in rural areas near Vellore Tamil Nadu, South India. Health education aims to change the behaviour of a community and of individuals in such a way as to improve their health. The theory of behaviour change has been deeply studied and the insights obtained from social psychology, sociology and anthropology are used in health education. One of the principles used is to "start from where they are." Education is not just like writing on black piece of paper. People already have their own ideas about what to do to maintain health, what is the cause of disease and how it should be treated. If one ignores these and tries to enforce only one's own point of view, one will not be very successful. To have any kind of meaningful communication is difficult if the individuals trying to communicate with each other have no shared background of common knowledge, attitudes or needs. One cannot expect the patients to immediately accept and adopt one's knowledge and attitudes, and therefore to know and un derstand their views is of the utmost importance.
Keywords: Rural development-South India